Incorporation of hydrophobic nanochitosan improves wear resistance of dental sealants - Kritika, Selvakumar; Jothimani, B.; Vidhya, Sampath; Sanjeev, Kavitha; Mahalaxmi, Sekar; Venkatachalapathy, B.; Sureshkumar, S. (International journal of polymeric materials, 2021)
This study evaluated the effect of addition of nanochitosan on the wear resistance of pit and fissure sealants. Hydrophobic N-(2-ethylhexanoyl)chitosan nanoparticles were synthesized, characterized, and added to commercial sealants. The sealants were subjected to customized abrasion test, followed by wear resistance analysis using weight loss measurement and 3-D profilometric methods. Analytical techniques confirmed the substitution. The particles ranged in size from 320 to 670 nm. Results showed a marginal improvement in the wear behavior of modified sealants compared to unmodified sealants. It can be concluded that this modification could prolong the life of these preventive restorations.